The peculiarities of German history : bourgeois society and politics in nineteenth-century Germany - Blackbourn, David, 1949-; Eley, Geoff, 1949- (History e-book project., 1984)
A well-written, stimulating ... piece of scholarship. In a major re-evaluation of the cultural, political, and sociological assumptions about the ""peculiar"" course of modern German history, the authors challenge the widely-held belief that Germany did not have a Western-style bourgeois revolution. Contending that it did indeed experience one, but that this had little to do with the mythical rising of the middle class, the authors provide a new context for viewing the tensions and instability of 19th-and early 20th-century Germany